The Role of the Kerapatan Adat Nagari Minang Kabau Regarding to Settle the Pusako Tinggi Land Dispute - Doris Rahmat, Adi Sulistiyono, Mohammad Jamin, Mulyanto (International Journal of Advanced Science and Technology, 2020)
This article discuss the settlement to the lawsuit of minangkabau custom in high pusako land“ulayat” .According to customs land disputes to resolve and customs ( pusako high ) be solved through Kerapatan Adat Nagari (KAN) as an institution with the resolution of disputes customary good dispute pusako and sako dispute . In resolved by means of mediation by all the heads of customary or within the judicial take it to the customary or with the density called the Kerapatan Adat Nagari ( KAN).The problem is how to act the role of the customs in minang kabau about lawsuit ulayat lands in the resolution . The methodology used the juridical sociological , by means of research that is descriptive , through the data sources , a data collection: documents and interview featuring sources and process data being processed and in qualitative analysis , in the resolution by Kerapatan Adat Nagari, a lot of community less satisfied with the ruling , even the parties are dissatisfied inserting a lawsuit to trial , sometimes the decision Kerapatan Adat Nagari contrast with the a court